The human dimension of biodiversity changes on islands - Nogue, S; Santos, AMC; Birks, HJB; Whittaker, R; Willis, K; Steinbauer, MJ (American Association for the Advancement of Science, 2021)
Islands are among the last regions on Earth settled and transformed by human activities and provide replicated model systems for analysis of how people affect ecological functions. By analyzing 27 representative fossil pollen sequences encompassing the past 5000 years from islands globally, we quantify rates of vegetation compositional change before and after human arrival. Following human arrival, rates of turnover accelerate by a median factor of nine, with faster rates on islands colonized in the past 1500 years than for those colonized earlier. This global anthropogenic acceleration in turnover suggests that islands are on trajectories of continuing change. Strategies for biodiversity conservation and ecosystem restoration must acknowledge the long duration of human impacts and the degree to which ecological changes today differ from pre-human dynamics.